Sequential Growth and Etching of Gold Nanocrystals Revealed by High‐Resolution Liquid Electron Microscopy. Issue 7 (18th February 2019) - Kim, Sang Yun; Dae, Kyun Seong; Koo, Kunmo; Kim, Daewoon; Park, Jungjae; Yuk, Jong Min
Abstract : Sequential growth and etching of Au nanoparticles in solution are observed in situ using the graphene liquid cell electron microscopy. Observation reveals that concentration of etching ions in aqueous growth solution leads transition from nanoparticle growth to its etching. At each step, the authors demonstrate different kinetics for both morphological evolutions and reaction rates. This study will likely benefit design strategies of nanoparticles with specific size or shape. Abstract : Graphene liquid cell electron microscopy probes sequential growth and etching of Au nanocrystals at an atomic level resolution. Concentration of etching ions depending on solution pH and radiolysis products of precursors and water switches nanocrystal growth process into etching process. Different morphological and kinetical changes are observed between growth and etching process.